Pengaruh Perubahan Kurikulum 2013 Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam - Nur Anisa; Nur Adelin; M. Fikri Istaqomaly; Darwis Darwis (Program Studi Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Islam 45, 2024)
This study aims to determine the policies and changes to Curriculum 13 for students, as well as educators' efforts to increase students' learning motivation in Islamic Religious Education subject class X IPS at SMAN 4 Bekasi. From the results of the study with a total sample of 15 people, it was obtained that the students' perceptions about the 2013 curriculum at SMAN 4 Bekasi had a positive phenomenon, as evidenced by the maximum sample value that obtained the lowest score of 30 with the highest score of 50, the sum score of 593, the total score the average (mean) is 39.53, and the standard deviation score is 6.632 (2) The learning motivation of students at SMAN 4 Bekasi has a positive phenomenon, as evidenced by the maximum sample value which obtained the lowest score of 28 with the highest score of 50, the sum score is 628, the average score (mean) is 41.87, and the standard deviation score is 6.770, (3) From the results of the moment product correlation test the relationship between students' perceptions of the 2013 curriculum and students' learning motivation is worth 0.799, which means that the coefficient value is 0.7 <0.9 = in the category of having a lower or weaker relationship between variables. Thus the results of the Summary Model are used to determine the relationship between two or more variables in the regression equation. Here what is seen is the R-Square value. The R-Square value in these results means that the effect of the 2013 Curriculum (X1) on Learning Motivation (Y) is 63.8%, the remaining 36.2% is influenced by other variables outside the model. The terms of the relationship between variables are good or not if the R-Square value is above 50% it means good, if it is below 50% it means it is badin evaluating the learning process that has been implemented.